Mapping service providers’ positions in the market - Exploring the field for evaluating technology consultancy firms - Andersson, Victor (My University, 2017)
Positioning a company in an industry provides opportunities for firms to differentiate themselves and provide additional value to their customers. In order to work efficiently with their positioning, keeping track of the different perceptions of the own company’s position is essential. This thesis aims to develop a model to help companies evaluate their position from the customers’ perspective. Additionally, the different perspectives on positioning have been examined together with possible ways to operationalize the model. As this model were developed in the technology consultancy industry with customers within process and manufacturing industries, it differs from earlier models. Previous attempts to evaluate positions and customers’ perceptions have been conducted in consumer markets where adoptions of positioning strategies are more common, which makes a model of this kind one rather unique. Also, many of the previous attempts to evaluate positioning is solely based on the managers’ perspective. This work has been conducted in an iterative manner where literature have been tested and adopted against the customers and employees in the context. Empirical findings together with previous literature have made the foundation on which the conclusions for this thesis have been drawn. The proposed model consists of 14 dimensions which have been found relevant to customers’ perceptions and the value that they perceive. Furthermore, it is argued for a more “value-related” position to be measured due to both the low operability and the weak link of the perceptions of positions (or image) and the customers’ purchase decisions. Additionally, the thesis has highlighted the different ways of finding discrepancies in perceptions between the different involved parties, and propose that finding and aligning the perceptions will be of highest importance in order to succeed with positioning. Finally, it is also proposed that the concept of positioning, and the width of the area, differs between customers and the own employees. Here, employees seem to use positioning in a much wider context and incorporate a more strategic manner. Customers on the other hand, seems to regard a set of areas (which they find relevant) when building their perceptions. Although, the customers view seems to only evaluate the facade of the company and the different areas of interactions through which they connect with their suppliers.
Keywords: Transport; Övrig industriell teknik och ekonomi; Transport; Other industrial engineering and economics